Social movements in perspective. Compared analysis of armed and student mobilizations and their incidence in the reconfiguration of the contemporary Mexican State (Revista de Investigaciones Universidad del Quindío, 2023)
The objective of this article is to carry out, from different explanatory paradigms, a comparative analysis of the impact of social movements in Mexico on the crisis and reconfiguration of the State and its derivations in the political system, both in its authoritarian facet and in its plural and democratic perspective. This is based on two types of movements: student movements and armed movements with different types of demands. We start from two types of movements: student movements and armed movements with different types of demands. For this purpose, the following are taken as subjects of study: the armed movements of Guerrero in the 1970s and the student movement of 1968, where their impact in the face of an authoritarian regime is deepened. At the same time, the self-defense movements in Michoacán are also analyzed as prototypes of social movements in a completely different framework in time and circumstance, but which have equally impacted the dynamics governing the State and the political system of our country. It is a comparative and transversal analysis of interpretative cut based on documentary sources related to the reconfiguration of the contemporary Mexican State. The resulting information was interpreted with the computer support of ATLAS ti, version 8. The findings of this research show that in the five cases transformations in the political dynamics of the State and in the way they were processed within the Mexican political system can be appreciated, which evidenced that social movements in Mexico have indeed served as a catalyst in the processes of political change that have gradually dismantled authoritarian schemes of political power, but also denote an institutional weakness to assimilate them.
Keywords: social movements; new social movements; State; political system; self-defense; México